Junctional epidermolysis bullosa: a case report - A. MOMENI & K. PIEPER (Paediatric Dentistry, 2005)
Epidermolysis bullosa (EB) describes a group of hereditary mechanobullous disorders which are all characterized by blistering of tissues containing stratified epithelia [1,2].